The role of bank loans and deposits in the monetary transmission mechanism in Malaysia - Kassim, Salina; Abdul Majid, M. Shabri (The Berkeley Electronic Press, 2009)

(untitled)
This study attempts to determine the importance of the banking sector in the monetary transmission process in a developing economy. The study analyzes the Malaysian data focusing on three sample periods: the entire sample period (1989:01-2006:12); the pre-crisis period (1989:01-1996:12); and the post-crisis period (1999:01-2006:12). To achieve this objective, the study relies on two tests: fi rst, the auto-regressive distributed lag (ARDL) model for the long-run relationship among the variables and second, the impulse response functions and variance decomposition analysis for the short-run relationship among the variables. The fi nding shows that both bank deposits and loans play crucial roles in the monetary transmission process in the economy, suggesting evidence for the money endogeneity theory of post-Keynesian economists. In particular, bank deposits and loans are shown to provide an important link from monetary policy to output. This underscores the importance of ensuring the soundness of banking system as a pre-requisite to economic stability in the absence of such market based tools as market-based actions on exchange rate or interest rates as monetary stabilisation tools.